Lirik Lagu “Citra Cinta” Karya Rhoma Irama: Kajian Stilistika - Moh Muzakka (Program Studi Sastra Indonesia, Fakultas Ilmu Budaya, Universitas Diponegoro, 2021)
The purpose of this research is to study the language style of Rhoma Irama's song lyrics entitled